Construcción del sujeto femenino: Una aproximación identitaria en las obras Al diablo la maldita primavera de Alonso Sánchez Baute y El lugar sin límites de José Donoso (2017)
Since the marginal literature started its peak moment in Latin America, new creations to perform reality have emerged from it; queer people have been assigned the main role of different literary pieces, showing their particularities and charm. Edwin Rodríguez and Manuela, main characters of Alonso Sanchez Baute’s Al diablo la maldita primavera and José Donoso’s El lugar sin límites are also a sample of this kind of literature. In the present case, the focus of attention is the construction of the feminine subject through the eyes of biological men, who think of themselves as women. It is the intention of the present paper to analyze the subjectivity of Edwin and Manuela and how they perform as women through their specific practices and the conceptual support of Foucault and Judith Butler.